A New Hybrid Sensor Design Based on a Patch Antenna with an Enhanced Sensitivity Using Frequency-Selective Surfaces (FSS) in the Microwave Region for Non-Invasive Glucose Concentration Level Monitoring - Köse, Umut; Sili, Güliz; Döken, Bora; Saygılı, Emre Sedar; Akleman, Funda; Kartal, Mesut (MDPI, 2026)
In this study, a hybrid sensor based on a defective square-truncated patch antenna (STPA) and a frequency-selective surface (FSS) was analyzed numerically and experimentally for different glucose–distilled water solutions. Here, an FSS was employed to enhance the sensitivity of the hybrid sensor. The sensing principle relies on monitoring variations in the loss tangent (tanδ) and relative permittivity (εr) caused by different glucose concentrations applied to the sample under test (SUT). An open-ended coaxial probe was used to measure the complex permittivity of the solutions, which was then fitted to the Debye relaxation model. The simulated and experimental results of the novel sensor showed good agreement in a glucose concentration monitoring application. The sensor spanned the glucose range from 0 mg/dL to 5000 mg/dL, exhibiting a sensitivity of 55.44 kHz/mgdL−1 and a figure of merit (FOM) of 6.23 × 10−4 (1/mgdL−1) in the experiments and 53.60 kHz/mgdL−1 and 1.71 × 10−4 (1/mgdL−1) FOM in the simulations. When solutions with different concentrations were tested in the SUT, the resonance frequency of the antenna ( f0, in GHz) changed. To further characterize the sensor response, the relationship between the glucose concentration (C, in mg/dL) and f0 was examined. A regression-based prediction model was constructed to map the measured scattering parameters to the glucose concentration, yielding a coefficient of determination (R2) of 0.976. The high sensitivity, compact size, and compatibility with planar fabrication suggest that the proposed hybrid sensor has the potential to contribute to the development of non-invasive glucose-monitoring systems.
Keywords: Hybrid Biosensor; Non-Invasive Sensor; Microstrip Antenna; Frequency-Selective Surface (FSS); Glucose Level Monitoring